IT'S THE MOST WONDERFUL TIME OF THE YEAR. UNLESS YOU LIVE IN NEW YORK. (Tufts Archival Research Center, 2007)
Marginalia; Draft; Draft of advertisement opposing a increase in cigarette taxes in New York. Says that New Yorkers already pay a lot of taxes. Argues that such an increase will lead to more smuggling and sales losses to other states. Questions the reliability of taxes from cigarettes.